(untitled) (Journal of Legal Studies, 2021)
In this study, we will analyze the instantaneous control in the recruitment of civil servants in the Republic of Kosovo. The purpose of the study is to achieve knowledge of the object of study, ie how the procedure of recruitment of civil servants is carried out, which procedures should be implemented until the establishment of employment in the civil service of Kosovo and which bodies are competent to control the legality of administrative acts of state administration bodies in the field of recruitment and establishment of employment of civil servants. Specifically the detailed aspects of the facility, ie how the recruitment is performed, how a labor relationship is established in the civil service of Kosovo, and how the control is applied internal versus the legality of administrative acts of public administration bodies in the field of recruitment of civil servants and by whom. The result of this study is the achievement with the knowledge of the object of study. In this study to achieve or not to confirm the hypotheses raised, we have used descriptive and statistical methods. Primary data are taken from the annual reports of the Ministry of Public Administration on the state of the civil service, the work reports of the Independent Oversight Board for Civil Service, literature, legal acts, and general normative acts governing the field of recruitment in civil service. The conclusion of this study is that the staffs in the civil service are not accepted according to the principle of merit, that the state administration bodies largely respect the deadlines for the establishment of labor relations, that there is no instantaneous control in the field of recruitment of civil servants. Had the proper influence on the heads of state administration institutions to recruit civil servants on the basis of merit.